Implementasi Metode Talaqqi Pada Program Tahfidz Al-Qur’an Juz 30 - Amalia, Nisa; Shopiyah, Siti (Prodi Pendidikan Keagamaan Islam, 2024)
This research is motivated by the fact that there are still many students who have not maximized their deposits and muroja'ah. The purpose of this research is to determine the implementation of the Talaqqi Method in the Tahfidz Juz 30 program, to determine the achievement process, to determine the inhibiting and supporting factors for the Tahfidz Al-Qur'an Juz 30 MI Al-Mu'awanah Petukangan Utara program. This research uses qualitative research methods with a descriptive approach. The results of this research show that the Talaqqi method can be applied well in the learning process, but the muraja'ah system has shortcomings and does not work optimally, due to the lack of students in muraja'ah. The evaluation form includes weekly and monthly assessments, PAT, PAS, and also the final Tahfidz exam. Supporting factors in the Tahfidz learning process are the existence of adequate student learning resources, the role of parents in supporting this memorization activity and the students' great willingness to memorize. The inhibiting factors are the influence of the environment and the influence of gadgets as well as laziness which causes students to not focus on memorizing and reciting.